SEMANTICS OF THE DEPICTION OF DAUGAVPILS IN ANITA LIEPA’S DOCUMENTARY PROSE AND FICTION - Meškova, Sandra (Via Latgalica, 2014)
Anita Liepa (born 1928) is a contemporary Latvian prose writer whose creative work was closely related to the post-soviet period in Latvia in the late 20th – and the beginning of the 21st century. In her works she depicted significant evidence of complex and contradictory processes in the history of Latvia in the 20th century, especially those related to World War II and its consequences for Latvia. Her works are divided into two distinct groups: documentary prose and fiction. The writer was born in Daugavpils, a town on the south-eastern border of Latvia, that had a significant role in the history of Latvia, especially in relation to World War II, as the town, was the place of dislocation of the major cavalry corps regiment in Daugavpils fortress. A. Liepa’s uncle Anatolijs Sondors was the fortress commandant, who faced the entrance of the Red Army and along with other Latvian army officers was deported to the Far North of the Soviet Union and died there.The present paper regards the depiction of the cultural space of Daugavpils in Liepa’s works, searching for parallels with the writer’s biography and views expressed in different media, that attribute specific connotations to the semantic of the topos of Daugavpils with border as its major dominant. The paper follows up the depiction of Daugavpils both in Liepa’s documentary prose (“Exhumation”, “Colt Years”, “Silenced Pages”) and fiction (“Windfall”). The paper is methodologically based on the notions of cultural geography, semiotics and feminist autobiography studies. It makes use of Mikhail Bakhtin’s term “topos” to denote a model of spatial construction. Border is singled out as the central element of the semantic of the topos of Daugavpils in Liepa’s works, focusing on its spatial, temporal aspects, as well as the depiction of culture environment.The topos of Daugavpils is most precisely and extensively depicted in the memory novel “Colt Years” („Kumeļa gadi”). Though published in 1993, the novel had actually been completed before any other of Liepa’s documentary works; this may partially be the reason, why she made depictions of Daugavpils in her following works more laconic. However, the major difference is determined by the genre of her works. In documentary prose the topos of Daugavpils reveals the information about the epoch or what may be called “signs of the time”, activating the culture code (according to Roland Barthes’ division of codes into hermeneutic, semic, proairetic, symbolic, culture codes), yet also developing a bond with the depiction of action and manifestations of the narrator’s subjective emotional states and the system of values. In works of fiction, space is a poetic category closely related to other poetic elements of the text, foregrounding the hermeneutic, semic, proairetic and symbolic codes. Hence, in “Colt Years” the topos of Daugavpils depicts not only the historical and cultural realia and landmarks of the town in the period of the 1930–1940s, but also spatial opposites of two homes the homodiegetic narrator lived in (her deceased father’s house, where she spent the happiest time of her childhood, and her uncle’s hous, where she lived during her school years), accentuating the bond between space and the narrator’s psycho-symbolic reality (referring to the semic and symbolic codes). The link between the topos of Daugavpils and the plot in all documentary works regarded is implied by the locus of Daugavpils railway station as a point of departure or arrival of characters involved in central plot lines. Scenery seen through the train window is realistically described in detail, providing place names, geographical names, referring to earlier episodes of characters’ lives. Thus, the proairetic code is activated along with the culture and other codes. The hermeneutic code is activated in the novel “Windfall” in a very interesting way. On the one hand, the author realistically describes the town of Daugavpils referring to historical events of the time of Awakening there; on the other, the toponym “Daugavpils” is replaced by an imagined name “Rūdunava”. Thus, the analysis of the depiction of Daugavpils in A. Liepa’s works leads to conclusions about the close connection between the category of space and the genre.